You need to convert the given equation of ellipse into its standard form `(x-h)^2/a^2 + (y-k)^2/b^2 = 1` , hence, you need to complete the squares such that:

`(x^2 - 2x + 1) + (4y^2 - 8y + 4) - 1 - 4 + 1 = 0`

Reducing like members yields:

`(x - 1 )^2 + (2y - 2)^2 = 4`

Dividing by 4 yields:

`(x - 1 )^2/4 + 4(y - 1)^2/4 = 1`

`(x - 1 )^2/4 + (y - 1)^2/1 = 1`

Since the length of...

(The entire section contains 196 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.